The Use Of Social Media Among English Language Sisc+ In Enhancing Professional Development Of Coachees In Malaysia - Yunus, Yusnita Md (2019)
qualified teacher has always been a demand to provide quality education. Through professional development programmes, teachers could upgrade their knowledge and skills to reach the quality standard. As one of the elements of professional development, coaching is capable at unlocking teachers' potential, making improvement, and reaching the standard. Concerning the quality of teachers, the Ministry of Education has introduced School Improvement Specialist Coaches (SISC+) to provide coaching to teachers in schools. Because of time and distance constraints, SISC+ are unable to have frequent visits.